Economy-Wide And Distributional Impacts of An Oil Price Shock On The South African Economy - Essama-Nssah, Boniface, 1949- 1949- (The World Bank, 2007)
As crude oil prices reach new highs, there is renewed concern about how external shocks will affect growth and poverty in developing countries. This paper describes a macro-micro framework for examining the structural and distributional consequences of a significant external shock-an increase in the world price of oil-on the South African economy. The authors merge results from a highly disaggregative computable general equilibrium model and a micro-simulation analysis of earnings and occupational choice based on socio-demographic characteristics of the household. The model provides changes in employment, wages, and prices that are used in the micro-simulation. The analysis finds that a 125 percent increase in the price of crude oil and refined petroleum reduces employment and GDP by approximately 2 percent, and reduces household consumption by approximately 7 percent. The oil price shock tends to increase the disparity between rich and poor. The adverse impact of the oil price shock is felt by the poorer segment of the formal labor market in the form of declining wages and increased unemployment. Unemployment hits mostly low and medium-skilled workers in the services sector. High-skilled households, on average, gain from the oil price shock. Their income rises and their spending basket is less skewed toward food and other goods that are most affected by changes in oil prices